A urokinase-activated recombinant anthrax toxin is selectively cytotoxic to many human tumor cell types - Abi-Habib, Ralph J. (2006)
Urokinase plasminogen activator (uPA) is a tumor-specific protease highly expressed in several types of solid tumors and rarely present on normal cells under physiologic conditions. Due to its high expression on metastatic tumors, several different strategies have been used to target the urokinase system. These have mostly led to tumor growth inhibition rather than tumor regression. A different approach was adopted by replacing the furin activation site on a recombinant anthrax toxin with a urokinase activation site. The resulting toxin, PrAgU2/FP59, was highly potent against tumors both in vitro and in vivo. In this study, we show that PrAgU2/FP59 is toxic to a wide range of tumor cell lines, including non–small cell lung cancer, pancreatic cancer, and basal-like breast cancer cell lines. Of the few cell lines found to be resistant to PrAgU2/FP59, most became sensitive upon addition of exogenous pro-uPA. PrAgU2/FP59 was much less toxic to normal human cells. The potency of PrAgU2/FP59 was dependent on anthrax toxin receptor, uPA receptor, and uPA levels but not on total plasminogen activator inhibitor-1 levels. In this study, we show that PrAgU2/FP59 is a wide-range, highly potent, and highly selective toxin that is capable of specifically targeting uPA-expressing tumor cells, independently of the tissue of origin of these cells. Furthermore, we identify three molecular markers, anthrax toxin receptor, uPA, and uPA receptor, which can be used as predictors of tumor cell sensitivity to PrAgU2/FP59. [Mol Cancer Ther 2006;5(10):2556–62]